European data market: the rise of individuals to the “Mount Olympus” of artificial intelligence or the “oiling” of the human being? - A. S. Rodrigues de Brito, Iolanda (UNIO – EU Law Journal, 2023)
This article aims to contribute to the debate on the long-term consequences arising from the creation of a European data market, considering the limitless potential of artificial intelligence (AI). Encouraging mass data production to develop AI could compromise the effective protection of personal data, the preservation of European liberal democracies and human rights, the promotion of innovation and even European economic prosperity. Bearing in mind the EU’s “spiritual and moral heritage”, enshrined in the Preamble of the Charter of Fundamental Rights of the European Union (CFREU), it is essential to ensure that we are truly walking along a path that will lead us to a democratic future.